Conocimientos y prácticas de lactancia materna exclusiva en puerperas del Centro de Salud de Mariscal Sucre, Milagro – Guayas en el periodo mayo - septiembre 2019 - Jijon Prieto, Erika Johana (2019)
The objective of the study was to establish the lack of knowledge of the postpartum women on exclusive breastfeeding of the Mariscal Sucre Milagro health center, the study design was cross-sectional -non-experimental quantitative under observation methods, description and analysis of medical records of the adolescents treated at the Mariscal Sucre Health Center. It was used as study population to 100 adolescents, intentional sampling technique was applied which allowed to select those woman with ignorance representing 75 cases, abtaining the following results: total ignorance of the importance of exclusive breastfeeding 49%,abandonment of breastfeeding after the six months of the RN 31%, and abandonment before the months of life of the RN 20%.